Engaging Students in Global Citizen Science: A U.S.-Japan collaborative watershed project. Issue 2 (4th March 2019) - Fujiwara, Yujiro; Hite, Rebecca; Wygant, Heather; Paulsen, Susan
Abstract : Innovative education approaches include citizen science projects that allow students to participate in locally relevant scientific work, connecting content to the real world. Global collaboration provides students with a broader perspective on local issues, allowing students to become more globally aware.